Síndrome de boca ardiente y su manejo terapéutico en adultos mayores de 20 años de edad. Revisión bibliográfica - Silva Armijos, Mayra Verónica (2023)
Burning mouth syndrome (BMS) is a chronic pathology characterized by nociplastic pain, accompanied by intraoral burning or a sensation of dysesthesia, without obvious causal lesions in the mouth. investigation and clinical examination, this pathology usually has a negative impact on the quality of the patients who suffer from it because its etiology and treatments are not yet well defined. The purpose of this study was to analyze burning mouth syndrome and its therapeutic management, establish the factors that are associated with the syndrome and determine the prevalence according to sex and age in adults older than 20 years. This study was bibliographical, descriptive and analytical. For this study, 39 bibliographic sources in English, Spanish and Portuguese were taken into account; between the years 2012 and 2022, which were selected through various databases such as Medline/PubMed, Google Scholar, VHL, Scielo, OVID, Elsevier, Springer; the information was organized and systematized in data tables for analysis. It was obtained as a result that this syndrome prevails in women between 50 - 64 years of age; the drug most used in pharmacological therapy is clonazepam and in non-pharmacological management, low-level laser therapy; factors mostly associated with BMS were depression and anxiety, followed by sleep disturbances, stress and endocrine disorders. Concluding that BMS is more prevalent in adulthood and in females, psychological disorders are related to this pathology; clonazepam and laser therapy are effective for BMS and a multidisciplinary approach is needed